Study of some properties of cyanopyridine derivatives in solutions (2015)
Some new cyanopyridine derivatives have been synthesized and their characterization was done by IR, 1H NMR and mass spectral data. Further, some physicochemical properties such as density, refractive index, conductance etc. have been studied for these synthesized compounds, in different solvents at 308.15 K.